EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS BUDAYA DI SMP ISLAM BANI HASYIM MALANG - Muhammad Adip Fanani; Fitrah Ainul Mawadah; M. Iqbal Abdurrohman (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
School culture is a place for carrying out all activities, activities, habits, customs and beliefs to internalize aspects of knowledge to students. The application of school culture aims to foster scientific values, have awareness and love for Allah SWT, be able to realize goodness and benefit for oneself, family, school, community and the entire universe, and strengthen students' love for the motherland, nation and country in Islamic framework. This research is a qualitative descriptive study. Data collected through observation and direct interviews. This research shows that the focus of learning evaluation at Bani Hasyim Malang Islamic Middle School is focused on three fundamental aspects, namely monotheism, nationality and universality. The results of the study show that evaluation of culture-based learning can foster a spirit of independence, awareness and movement within students. These three elements are interrelated with each other so that the nuances of the integration of religion and science (natural and social) have extraordinary significance and the pillars of religious culture can be internalized consistently.